Solving Burglary Offences: Building a Model to Predict Clearance of Burglary Following Initial Investigation. (21st February 2019) - Olphin, Tom W L; Bandyopadhyay, Siddhartha; Banerjee, Anindya
Abstract: This research identifies solvability factors for burglary offences, and develops previous research by building, and testing, an algorithmic prediction model for solvability of burglary offences. It is based on a full population of 9, 655 burglary offences reported to a UK Police force between 1st April 2012 and 30th April 2015. The dataset was split in half, with half being used to build the model and half to test it. Thirty-one solvability factors were identified, along with nine case-limiting factors, allowing a logit model to be built to predict solvability of burglary offences. When compared to a model of investigating all burglary offences, use of this model would reduce investigative workload by up to 42.2%, or 1, 321 cases per year.